Improvement of Creative Thinking Ability of Elementary Teacher Education Students in Utilizing Traditional Games in Social Studies Learning - Arga, Hana Sakura Putu; Nurfurqon, Faridillah Fahmi; Nurani, Riga Zahara (Mimbar Sekolah Dasar, 2020)
Creative thinking skills of elementary teacher education students' needs to be improved in a fun social studies learning process. One of the lessons that can make learning a pleasant atmosphere is to apply knowledge by applying traditional games. This research aims to increase the creativity of elementary teacher education students in utilizing traditional games to preserve the nation's culture. The research method used was a quasi-experimental design with a nonrandomized pretest-posttest control group. The instrument used in this study was a tablet-shaped observation instrument. This research shows that learning science by applying traditional games can improve elementary teacher education students' creative thinking skills. It can be seen from the learning outcomes of elementary teacher education students social studies using traditional games that are better than conventional learning.